ПРАКТИКООРІЄНТОВАНИЙ ПІДХІД У ПІДГОТОВЦІ МАЙБУТНЬОГО ВЧИТЕЛЯ ЯК ЗАСІБ ПІДВИЩЕННЯ ЯКОСТІ ОСВІТИ (Педагогіка вищої та середньої школи, 2007)
The article substantiates necessity to use such an approach to training of future teachers which is orientated towards practical application. It is essential as a means to provide high quality cf training in universities' educational process.